Root Cause Analysis Using Fishbone Diagram: Company Management Decision Making - Siti Holifahtus Sakdiyah; Nurafni Eltivia; Aang Afandi (PT. EQUATOR SINAR AKADEMIA, 2022)
This study aims to analyze the causes of delays in decision-making within the company. Managers can identify several constraints in decision-making by using analytical tools. In this study, the device used to analyze the problem is root cause analysis. Root cause analysis is used to determine the initial cause of the issues. The method used in the root cause analysis is a fishbone diagram where the fishbone diagram can identify some of the problems that underlie the constraints in decision making. This study uses a qualitative descriptive method by taking data from interviews and documentation. The results of this study can be seen in decision making four problems underlie the inhibition of decision making. The problem is the first decision-maker; namely, the company's management is not wholly a determinant in making decisions. The second problem is that the information presented as a guide for decision-making is inaccurate, not timely, and irrelevant. The third problem is the absence of software that processes data into information needed by company management. The last problem is the lack of integration between divisions, so the resulting information is out of sync. Root cause analysis and fishbone diagrams, that was possible to analyze in detail the causes of delays in decision making. In the end, management can find solutions to each of these problems. Management will search each problem for the root cause, and the answer that they will give will be right on target so that the hope to minimize the obstacles to decision making will be implemented.